THE INFLUENCE OF COMPENSATION AND OCCUPATIONAL SAFETY AND HEALTH ON ONLINE OJEK DRIVER PERFORMANCE PRODUCTIVITY IN MEDAN CITY (Study of Go-Jek, Grab, and Maxim Online Ojek Drivers) - Zahara, Mutia; Sinaga, Aprizal Haris; Dalimunthe, Ritha F. (Strategic Management Business Journal, 2023)
This study investigates the impact of compensation, occupational safety, and health on the productivity of online motorcycle taxi drivers in Medan City, utilizing a quantitative methodology. The research, encompassing 99 respondents from Go-Jek, Grab, and Maxim, employs multiple regression analysis, revealing a significant positive impact of compentations and Occupational Health and Safety (OHS) on driver productivity across all platforms. The findings underscore that enhancing compensation and prioritizing safety and health are effective strategies for increasing productivity. The study suggests companies offering online motorcycle taxi services should develop policies to enhance the welfare and performance of drivers. Acknowledging the study's limitations, future research should consider additional factors for a comprehensive understanding. .  JEL Classification: L21, L23, L25